1988
DOI: 10.1192/bjp.152.6.820
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate on the Prevalence of Mania

Abstract: Monthly rates of admission of manic patients to the Department of Psychiatry in Galway Regional Hospital were examined for a five-year period. Monthly variation in admission rates was compared with monthly levels of sunshine, temperature and daylength. Results indicated a significant seasonal variation in the prevalence of mania: admission rates were higher in the sunnier months and in months with a greater average daylength. It is suggested that the presentation of mania in this fashion is due to an abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…Winter and summer are the main seasons when temperatures drop to as low as -3°C during winter and reaches 46°C or higher during the summer, with scanty rainfall, plenty of sunshine during the whole year and variation of day length throughout the year. Little variability in variables other than temperature confirms Carney et al, findings that both sunshine and day length, but not temperatures, correlated significantly with admissions for mania rate [6]. The authors suggested that the onset or relapse of mania may be due to an abnormal response to increasing exposure to light.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Winter and summer are the main seasons when temperatures drop to as low as -3°C during winter and reaches 46°C or higher during the summer, with scanty rainfall, plenty of sunshine during the whole year and variation of day length throughout the year. Little variability in variables other than temperature confirms Carney et al, findings that both sunshine and day length, but not temperatures, correlated significantly with admissions for mania rate [6]. The authors suggested that the onset or relapse of mania may be due to an abnormal response to increasing exposure to light.…”
Section: Discussionsupporting
confidence: 54%
“…Myers and Davies [5] reported on the seasonal incidence of mania and its relationship to climatic variables and found a significant annual cycle with a peak in summer and trough in winter, the current month temperature being the best predictor of mania admission rate. In the study conducted by Carney et al [6], the influence of climate on the prevalence of mania demonstrated a striking peak during spring and summer, with a decline in autumn and increase again during winter. They also found that sunshine and day length correlated significantly with mania admission rates while current month temperatures did not.…”
mentioning
confidence: 95%
“…There have been suggestions of an increased light sensitivity, during spring and summer, in susceptible individuals [3,5], and evidence of a genetic factor determining seasonality of mood and behavior [27].…”
Section: Discussionmentioning
confidence: 99%
“…53 It is also noteworthy that seasonality of psychiatric disorders itself could have influenced our results, which may be reflected by the peak in August of panic attacks 54 associated with the increase of manic/hypomanic episodes. 55,56 In our ED we have observed a slight decrease of total visits during summer months in the last fifteen years, with July and August exhibiting a 5 to 8% lower prevalence than March or November. Therefore, we can not explain our findings in terms of correlation with increase of total ED visits.…”
Section: Articlementioning
confidence: 64%